Effect of four selected carrier solvents on embryonal stages of Danio rerio - Chromcova, Lucie; Stepanova, Stanislava; Plhalova, Lucie; Praskova, Eva; Svobodova, Zdenka (Neuro endocrinology letters, 2012)
OBJECTIVES: The aim of this study was to determine the effects of 96 hour exposure to selected solvents on the embryonic stages of zebrafish (Danio rerio). We investigated mortality and various types of changes which appeared (oedema, tail and eye defects, weak pigmentation, and deformation of the body). Based on the results, values of NOEC and LOEC for embryos of D. rerio were determined. METHODS: Embryonal toxicity tests were conducted according to OECD guideline 212. Ethanol and methanol were tested at concentrations of 0.1, 0.5, 1, 1.5, 2%; acetone at concentrations of 0.1, 0.5, 1, 1.25, 1.5%; and dimethylsulfoxide at concentrations of 1, 1.5, 2, 2.5, 3%. RESULTS: The LOEC values of ethanol and methanol were detected in the 1% concentration. Statistically significant changes (oedema) were reported in 1% ethanol, and oedema, weak pigmentation and deformation of the body were observed in 1% methanol. After exposure to acetone, the most common occurrence of oedema was in the 0.5% concentration (LOEC = 0.5%). The solvent dimethylsulfoxide caused oedema and body deformation at the 2% concentration (LOEC = 2%). CONCLUSIONS: The NOEC concentrations of the individual solvents were as follows: ethanol and methanol, 0.5%; acetone, 0.1%; and dimethylsulfoxide, 1.5%. These concentrations of individual solvents were higher than the maximum recommended concentration for toxicity tests on fish. For this reason, it can be assumed that the concentration of solvent allowed by the norm does not affect the procedure or results of such tests.
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; embryo nesavčí; pigmentace kůže; testy toxicity; ethanol; Embryo, Nonmammalian; Skin Pigmentation; Methanol; abnormality očí; Ethanol; edém; Dimethyl Sulfoxide; Eye Abnormalities; aceton; Edema; dimethylsulfoxid; zvířata; Zebrafish; dánio pruhované; Acetone; rozpouštědla; methanol; mnohočetné abnormality; Abnormalities, Multiple; Solvents; Toxicity Tests; Animals